2018
DOI: 10.1111/tri.13280
|View full text |Cite
|
Sign up to set email alerts
|

Safety of dual kidney transplantation compared to single kidney transplantation from expanded criteria donors: a single center cohort study of 39 recipients

Abstract: Our objective was to compare the outcomes of dual kidney transplanataion (DKT) to single kidney transplantation (SKT) performed with grafts from expanded criteria donors (ECD) in recipients ≥65 years, focusing on surgical complications. All kidney transplantations (KT) performed between 2006 and 2014 in our institution were analysed. DKT was indicated according to the criteria of the French national Agence de la Biomedecine. Thirty-nine DKT and 155 SKT were included, with a median follow-up of 36 and 26.5 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Dual kidney transplantation is a valuable alternative to single kidney transplantation from expanded criteria donors. [76][77][78][79][80] Various techniques have been described, including bilateral placement, unilateral placement with separate anastomoses, and unilateral placement with patch anastomoses, [76][77][78][79][80] with comparable graft and patient survival and postoperative complications. 77 In the large series of 100 unilateral dual kidney transplantations, Ekser et al 76 reported seven patients (7%) with wound dehiscence and only one (1%) with incisional hernia.…”
Section: Kidney Transplant Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Dual kidney transplantation is a valuable alternative to single kidney transplantation from expanded criteria donors. [76][77][78][79][80] Various techniques have been described, including bilateral placement, unilateral placement with separate anastomoses, and unilateral placement with patch anastomoses, [76][77][78][79][80] with comparable graft and patient survival and postoperative complications. 77 In the large series of 100 unilateral dual kidney transplantations, Ekser et al 76 reported seven patients (7%) with wound dehiscence and only one (1%) with incisional hernia.…”
Section: Kidney Transplant Surgical Techniquementioning
confidence: 99%
“…Dual kidney transplantation has been associated with an increased incidence of wound complications compared with single transplantation (32% vs 10%, respectively, P = .009), 79 probably due to the prolonged operative time, 7 older recipient age, and the two incisions, although a recent study did not confirm such an association. 80 More than 10% of kidney transplant recipients receive a retransplantation. The surgical technique is similar to first-kidney transplantation, and usually, the second graft is placed in the contralateral iliac fossa.…”
Section: Kidney Transplant Surgical Techniquementioning
confidence: 99%
“…Multiple studies of short and long-term success with adult DKT have been reported since the early 2000s (Table 3 cites literature since 2015) [64–82,83 ▪▪ ,84]. Many of these studies focused on identifying appropriate selection criteria for DKT including not only prerecovery but also postrecovery (anatomy, histopathology, and preservation) factors.…”
Section: History Of Dual Kidney Transplantationmentioning
confidence: 99%
“…‘Old-for-old’ transplants and the Eurotransplant Senior Program, which was originally implemented in 1999, have played a prominent role in conjunction with DKT, particularly from a recipient selection perspective [15,24,28,85]. Centers in France, Germany, and the United Kingdom have likewise provided important contributions to the world experience in DKT including the use of alternative scoring systems and expansion with DCD donor kidneys [36,37,51,52,60,64,65,77,79,83 ▪▪ ]. In addition, centers in Ireland, Canada, Australia, Czech Republic, the Middle East, and Asia have reported valuable experiences with DKT [38,70,71,78,80–82,86].…”
Section: The International Experience With Dual Kidney Transplantationmentioning
confidence: 99%